Enteric bacteria in aerobically digested sludge. - Farrah, S R (1984)
Indicator bacteria, Salmonella spp., and total aerobic bacteria were determined in samples of undigested sludge and sludge that had been treated by one or two stages of aerobic digestion. Aerobic sludge digestion reduced the level of indicator bacteria by 1 to 2 log10 per g. The level of Salmonella spp. was also reduced during aerobic treatment of sludge. In general, aerobic treatment of sludge reduced, but did not eliminate, indicator bacteria and Salmonella spp.